PEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI KESEBANGUNAN MELALUI PEMBELAJARAN COOPERATIVE TIPE NUMBERED HEADS DISERTAI LKS - Ramadhani, Dwi; Haryono, Yulia; Lovia, Lita (Pendidikan Matematika, 2013)
The research is introduced by the lack of the students understanding of mathematical concept and students prefer to copy paste their friends exercise without paying attention it is right or wrong. This research is aimed to know the students understanding of mathematicalconcept by using learning model of Cooperative type Numbered Heads with LKS better than the students understanding concept by using conventional learning at class IX SMP PERTI Padang. The type of this research is experiment. Population in this research is students class IX SMP PERTI Padang who registered in academic year 2013/2014 that consists of three class. The tecgnique of sampling is random and selected class IX.1 as an experimental class and class IX.2 as control class. Insrument used was final test contain mathematical concept umderstanding indicators in the from of essay. Technique of data analysis used was Mann-Withney test with MINITAB sofware. Based on the hypothesis obtained P-value = 0,003, because p-less than Î± = 0,05 so the hypotesisis accepted the students understanding of mathematical concept by using Cooperative type Numbered Heads learning with LKS is better than students understanding mathematical concept by using conventional learning at class IX SMP PERTI Padang.